Aspects of the formation of encephalopathy and myocardiopathy in sepsis - M. V. Petrova; A. V. Butrov; V. V. Kulabukhov; D. V. Cheboksarov; O. V. Ryzhova (Вестник анестезиологии и реаниматологии, 2023)
Relevance. The severe brain damage in most cases leads the patient to a long-term chronic critical condition (CCS). Regardless of the underlying  disease that led to CCS, patients will have a certain imbalance of neurohumoral regulation and characteristic cognitive, muscle-reflex disorders.  This cohort of patients is characterized not only by a cascade of typical pathological processes in the brain, but also by the consistent involvement of  the cardiovascular system, respiratory organs, digestive organs, water metabolism, hormonal regulation, immunity, the addition of infectious-septic  complications closes the circle of pathological processes, which often leads to death. Materials and methods. The search for domestic publications was carried out in the database on the RSCI website, foreign – in the PubMed, Google  Scholar databases in the period 2000–2023. When analyzing the PubMed database, the query «sepsis neuroinflammation» found 5272 links. We  also studied works on the following keywords: «neurotransmitters and sepsis». Publications describing the clinical picture, diagnosis, and sepsis  were analyzed. A total of 40 articles were analyzed Such systems as immune, nervous and endocrine are interconnected due to regulatory peptides. Stable functioning of the central nervous system  (CNS), or rather adequate secretion of neuropeptides are necessary for a normal immune response. Neuronal anti-inflammatory regulation of tissue  macrophages is characterized by a local, rapid response to the pathogen through neuromediators.Confirmation of the neuropeptide theory of immunity regulation is the verification of neuropeptide receptors on peripheral blood lymphocytes and  monocytes. These results indicate a possible mechanism of a «vicious» circle that occurs in infectious-septic complications and leads to damage to  vital organs.To date, there are no widely available means for accurate monitoring of brain function at the patient’s bedside. There is no evidence or recommendations  to support monitoring of cerebral perfusion or function in sepsis patients. At the same time, modern research on the phenotyping of patients taking  into account brain dysfunction (sepsis associated encephalopathy) is based on the basic postulates of the pathophysiology and biochemistry of  sepsis, but does not offer any methods of instrumental diagnosis of this condition, except for the use of validated delirium, coma scales (Glasgow  coma scale, FOUR, CAM-ICU, etc.). Despite the described pathogenesis, there is currently no single definition of cardiac cardiomyopathy. However, most authors describe the fundamental  features of this pathology: acute reversible one- or two-ventricular systolic or diastolic dysfunction with reduced contractility, not due to coronary  heart disease. Primary cellular myocardial dysfunction in sepsis can manifest in several ways, including impaired function of the left and/or right  ventricles during systole or diastole, as well as with insufficient cardiac output (CO) and oxygen delivery. To explain the changes in myocardial  contractility associated with sepsis, several mechanisms have been proposed taking into account the host response. Since most of the parameters  of the echo signal depend on the conditions of the volemic status, the evaluation of the echo signal should be repeated at several time points and  supplemented with the definition of cardiac biomarkers. Conclusion. Analyzing the literature data on sepsis-associated encephalopathy and septic cardiomyopathy, it is possible to judge the interconnectedness  of these events indirectly through damage to neurons during infectious-septic complications. Especially neuro-humoral mechanisms of regulation of  the response to an infectious agent should be evaluated in patients with CCS, not only relying on laboratory diagnostics, but also using instrumental  methods of visualization of brain, heart, and kidney damage. Such methods include magnetic resonance imaging (MRI), electroencephalogram  (EEG), cerebral oximetry (CMRO2), echocardiography, ultrasound examination of the kidneys, etc